Militarização de escolas estaduais goianas: faces ocultas da privatização - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This dissertation developed in the Postgraduate Program in Education at the State University of Goiás, in the line of research on Work, State and Educational Policies, has as its theme the militarization of state schools in Goiás, with the objective of providing evidence of privatization of public basic education. and the public x private dichotomy in the process, through the handover/transfer of management of public schools to the Military Police. From a methodological point of view, the research is of a qualitative, documentary nature and the analysis of the following sources was carried out: decrees, ordinances, terms of technical cooperation between the State Department of Education of the Government of Goiás and the Military Police Teaching Command, as well as the internal regulations of the CEPMG. Methodologically, an analysis was made of documents and legislation that implemented and organized the State Military Police Colleges (CEPMG), looking for signs of privatization of the public in the process of militarization of state schools. For the theoretical foundation of this research, we refer to authors/theorists who support us in understanding the following categories: public-private and privatization of the public. We base our discussion on the works of Peroni (2021), Adrião et al (2009;2016), Adrião (2018) and Adrião and Domiciano (2021). For the discussion on neoliberalism and neoconservatism we use the works of Apple(2003), Dardot and Laval(2016), Freitas (2018), Brown (2019) and Miranda(2020) and to support the discussion on the process of militarization of education in Goiás we have the works Alves, Toschi e Ferreira(2018), Santos e Cara(2020), Alves e Oliveira(2020), Alves, Reis, Silva Santos e Ferreira(2021) and Alves, Santos e Bordin(2023). In this way, the research showed that the process of militarization of state schools in Goiás presents signs of a specific form of privatization of public education.
Militaryzation of goianas state schools: hidden faces of privatization
Keywords: Colégio Militar; Goiás; Público-privado; Privatização do público; Public-private; Privatization of the public; Military School; CIENCIAS HUMANAS::EDUCACAO; PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL